Composition of intestinal flora affects the risk relationship between Alzheimer's disease/Parkinson's disease and cancer - Hang, Zhongci; Lei, Tong; Zeng, Zehua; Cai, Shanglin; Bi, Wangyu; Du, Hongwu (Biomedicine & pharmacotherapy, 2022)
An increasing number of epidemiological studies have shown that there is a significant inverse relationship between the onset of Alzheimer's disease/Parkinson's disease (AD/PD) and cancer, but the mechanism is still unclear. Considering that intestinal flora can connect them, we tried to explain this phenomenon from the intestinal flora. This review briefly introduced the relationship among AD/PD, cancer, and intestinal flora, studied metabolites or components of the intestinal flora and the role of intestinal barriers and intestinal hormones in AD/PD and cancer. After screening, a part of the flora capable of participating in the occurrence processes of the three diseases at the same time was obtained, the abundance changes of the special flora in AD/PD and various types of cancers were summarized, and they were classified according to the flora function and abundance, which in turn innovatively and reasonably explained the fact that AD/PD and cancer showed certain antagonism in epidemiological statistics from the perspective of intestinal flora. This review also proposed that viewing the risk relationship between diseases from the perspective of intestinal flora may provide new research ideas for the treatment of fecal microbiota transplantation (FMT) and related diseases. [Display omitted] •The relationship between AD/PD and cancer risk is antagonistic.•Both AD/PD and cancer have bidirectional connection with intestinal flora.•Some intestinal flora and its metabolites play different roles in AD/PD and cancer.•Intestinal barriers and gut hormone are involved in the regulation of diseases.•Changes of intestinal flora may be a factor affecting the disease risk relationship.